A comprehensive review of topologies for photovoltaic I–V curve tracer. (15th January 2020) - Zhu, Y.; Xiao, W.
Abstract: The I–V curve tracer is an instrument that captures the I–V characteristics of photovoltaic (PV) generators corresponding to variable environmental conditions. The device is widely used to evaluate power generation performance and detect the fault conditions of PV power generators. Various I–V tracer techniques have been developed and proposed to trace the IV characteristics and ensure high accuracy and fast speeds. A comprehensive classification and analysis was undertaken to identify the advantages and disadvantages of different technologies. This study proposes and uses five performance indices to evaluate the performance of I–V tracers. The quantitative fidelity of commercial I–V tracers were also reviewed and evaluated. This paper serves as a valuable reference tool that should be used to guide the direction of future research and lead future improvements in the field.